TINJAUAN TERHADAP MOTIVASI WISATAWAN BERKUNJUNG KE OBJEK WISATA AIR TERJUN AEK MARTUA KABUPATEN ROKAN HULU PROVINSI RIAU - Sari, Fitria; Ibrahim, Mariaty; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The research is to find out what are the motives and the motivators that influenced tourist to visit Aek Martua waterfall.This research is uses descriptive quantitative methods to analyze problem which is going to conducted. The sample of this research was 100 people were taken by using accidental sampling. Then the data collection techniques in this is reseach the writer used observation, interview and quisionnaires. The writer using the likers scale as an instrument to measuring the lenght of intervals that can be used to find quantitative data.Based on the result of the research are the influence of motivator is more motivate tourists to visit Aek Martua waterfall than the motives. And, according to responden the motivation of tourists to visiting Aek Martua waterfall is good.Keyword: Motivation, motif and motivator, tourist